UPAYA PEMBANGUNAN CITRA ORMAS ISLAM MODERAT ORGANISASI NAHDLATUL ULAMA (NU): Studi Tentang Motif Perilaku Moderasi Beragama Para Kader Nahdlatul Ulama (NU) Di Kecamatan Trawas Kabupaten Mojokerto - Muzakki, Jauhari Fatkhul (Paradigma, 2022)
This research is motivated by the attitudes and views of the cadres of the Nahdlatul Ulama (NU) organization in Trawas District, Mojokerto Regency, who oppose and criticize the activities of other Islamic mass organizations, which are considered to have attacked the Nahdlatul Ulama (NU) organization and the Unitary State of the Republic of Indonesia (NKRI). This is in stark contrast to the concept of moderate Islam which has always been promoted by the Nahdlatul Ulama (NU) organization. So the jargon and claims of being a "moderate Islamic mass organization" by the Nahdlatul Ulama (NU) organization so far tend to lead to mere imagery. Therefore, through the perspective of social motive theory put forward by Alfred Schutz, this study explores the motives of the cadres of the Nahdlatul Ulama (NU) organization in campaigning for the jargon or motto of "moderate Islamic organizations". So the purpose of this research is to find out how the motives and motives of the efforts to build the image of "moderate Islamic organizations" are carried out by the cadres of the Nahdlatul Ulama (NU) organization in Trawas District, Mojokerto Regency. The approach used in this research is using a qualitative approach. While the results of this study indicate that the application of religious moderation, especially to people of other religions, has been going very well, while fellow Islamic organizations often face certain problems caused by several differences in the selection of arguments in the guidelines or basic religious foundations, the selection of methods and methods of da'wah, and different organizational labels. The motives for the efforts to build the image of moderate Islamic organizations carried out by the cadres of the Nahdlatul Ulama (NU) organization include; a) The form or form of respect, obedience, and total trust as a santri to the Kiai Nahdlatul Ulama, b) There is a decline in the quality of the cadres of the Nahdlatul Ulama organization, c) The potential or negative impact of the radicalism movement in Indonesia. Meanwhile, the motives for the efforts to build the image of moderate Islamic organizations carried out by the cadres of the Nahdlatul Ulama (NU) organization include; a) The defense fortress of the Nahdlatul Ulama organization and the Indonesian State, b) Encouraging the structural and cultural cadres of the Nahdlatul Ulama organization, c) Devotion as a santri to the Kiai Nahdlatul Ulama.